STRATEGI KETIDAKSANTUNAN DALAM VIDEO DEBAT PEMILIHAN PRESIDEN TAHUN 2019 - Gustiani, Tia; Aslinda, Aslinda; Usman, Fajri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
The goal of this article is to identify and explain impoliteness strategies in the 2019 presidential election debate and to evaluate the role of impoliteness used in the 2019 presidential debate. Qualitative descriptive is the kind of method that used by the researcher. The data was gathered from four YouTube videos of the 2019 presidential election debates and analyzed using the distributional and identity methods. This study used the theory of impoliteness by Jonathan Culpeper (2005) which withhold politeness, sarcasm or mock politeness, negative impoliteness, positive impoliteness, dan bald on record impoliteness. Based on the research result, it is found negative impoliteness was the most frequent impoliteness strategy, accounting for 43%. The speaker demonstrated his superiority by accusing and condemning the flaws of others in this strategy.Keywords: Impoliteness, Impoliteness Strategies, Debate, Election